Identification of CAP genes in finger lime (Citrus australasica) and their role in plant responses to abiotic and biotic stress - Lamiaa M. Mahmoud; Nabil Killiny; Manjul Dutt (Scientific Reports)
Abstract The study focuses on the in silico analysis of cysteine-rich secretory proteins and PR1-like (CAP) genes in finger lime (Citrus australasica), a citrus species known for its tolerance to Huanglongbing (HLB). We identified several PR1-like genes, all belonging to the CRISP family within the CAP superfamily. Of them, CaCAP2 transcript levels increased by over 300-fold in the finger lime compared to ‘Valencia' sweet orange upon infection with ‘Candidatus Liberibacter asiaticus' (CaLas). Localization studies using an EGFP fusion showed that the CAP2 protein is predominantly located in the nucleus, extracellular and plasma membrane. The study also examined CAP2 transcript levels in response to cold, drought stress, and salicylic acid application. Despite environmental stress causing apparent damage, CAP genes seem to play a significant role in managing both biotic and abiotic stresses. Analysis of CAP2 gene promoters from finger lime and sweet orange revealed 95.33% sequence identity, with variations in transcription factor-binding sites and cis-acting elements such as Stress Response Element (STRE: AGGGG), which might influence the differential expression of CAP2 between the two species. Additionally, expressing the finger lime-derived CaCAP2 gene in transgenic Nicotiana tabacum induced a strong defense response against Pseudomonas syringae pv. Tabaci., underscoring the CAP gene's crucial role in plant defense mechanisms against bacterial pathogens.